Integrale, Longueur, Aire de Henri Lebesgue - Otero-Garcia, Sílvio César [UNESP] (2015)
This thesis deals with the translation and analysis of Henri Lebesgue doctoral thesis, Integrale, Longueur, Aire. Published in 1902, this thesis presents the Lebesgue measure theory and integration named after him. The translation, intended to be as faithful to the original as possible, is based on Vinay and Darbelnet’s (1977) methodology. The analysis is developed from the theoretical reference of the deep hermeneutics, more specifically, Thompson (2011). Our intention is to make available an original source in Portuguese to help with Brazilian studies in History of Mathematics and also ease its use as na educational tool for math teaching.